2011
DOI: 10.1248/yakushi.131.453
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of P-gp Expression after Intestinal Ischemia-reperfusion Following 16-h Fasting in Rats

Abstract: Alteration of P-glycoprotein (P-gp) expression in‰uences the pharmacokinetics of P-gp substrates after intestinal ischemia-reperfusion (I/R). Fasting before intestinal I/R aŠects intestinal I/R injury. However, the eŠect of fasting on the alteration of P-gp expression after intestinal I/R has not been clariˆed. We previously reported that P-gp expression was altered after intestinal I/R following feeding. In the present study, we investigated the expression of P-gp after intestinal I/R following 16-h fasting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…These results suggested that IL-6 is one of main causes of the decrease in MRP2, FXR, PXR and CAR expression levels. We previously reported the alteration of malondialdehyde (MDA) level, which is a marker of organ injury after I/R, in the liver (28). The increase in MDA level was associated with the increase in IL-6 and with the decrease in MRP2, FXR, PXR and CAR expression levels, suggesting that the decrease in FXR, PXR and CAR expression levels, at least in part, might be caused the liver injury after intestinal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that IL-6 is one of main causes of the decrease in MRP2, FXR, PXR and CAR expression levels. We previously reported the alteration of malondialdehyde (MDA) level, which is a marker of organ injury after I/R, in the liver (28). The increase in MDA level was associated with the increase in IL-6 and with the decrease in MRP2, FXR, PXR and CAR expression levels, suggesting that the decrease in FXR, PXR and CAR expression levels, at least in part, might be caused the liver injury after intestinal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of ROS-induced oxidative damage was assessed indirectly by measuring the level of malondialdehyde (MDA), an intermediate product of lipid peroxidation, as described previously (15). For this study, a PBS suspension of Caco-2 cells and tissue homogenate were used.…”
Section: Oxidative Injury Assessmentmentioning
confidence: 99%
“…Evaluation of oxidative stress through determination of malondialdehyde (MDA) levels was performed as described previously (Ogura et al, 2011). Thiobarbituric acid (TBA) solution consisted of 2.6 mM TBA, 918 mM trichloroacetic acid, 0.3 mM HCl and 1.8 mM 2, 6-di-tert-butyl-4-metylphenol in 22% ethanol.…”
Section: Evaluation Of Oxidative Stressmentioning
confidence: 99%